COORDINATION BETWEEN REGIONAL DEVICES IN THE MANAGEMENT OF INTERESTED INDONESIAN MIGRANT WORKERS IN MALAKA DISTRICT - Maria Serafina Luruk Seran; Alo Liliweri; Nursalam - (Postgraduate School, Universitas Nusa Cendana, 2022)
Coordination is a basic function of management which explains the orderly unification of actions in the implementation of activities. In government organizations, coordination is needed to ensure that the implementation of government programs becomes more focused. One of the programs that requires coordination is the Management of Indonesian Migrant Workers (PMI) which is carried out in Malacca Regency. In this study, researchers will examine the Coordination between Regional Apparatuses in the Management of Retired Indonesian Migrant Workers in Malacca Regency with the aim of describing and Coordination between Regional Apparatuses in the Management of Retired Indonesian Migrant Workers in Malacca Regency. The theory used as the basis for researchers in this study is the theory of management functions according to Luther Gulick, known as POSDCORB and is an indicator in this research, namely: Planning, organizing, staffing, directing, controlling, reporting and budgeting. This research is qualitative. The informants selected purposively were 11 people. The research findings show that all informants know the purpose of the full PMI empowerment program but not all informants know what activities will be carried out in the full PMI empowerment program; technically there are 3 related areas in the program; coordinating the program is the field of training and placement of workers; there is no agreement in the meeting so far; the preparation of reports is only carried out by the field of training and placement of workers; not all related fields have budgeted special funds for retired PMI. The conclusion of this study is that so far the coordination between fields related to the empowerment of retired PMI has not been going well. Suggestions from researchers are that for a program to run well, continuous coordination is needed so that all parties involved can know what will be planned, carried out, and the extent of its implementation.